Novel Insights Into the Immune-Regulatory Functions of Mast Cells in the Cutaneous Immune Response - Honda, Tetsuya; Keith, Yuki Honda (Frontiers in Immunology, 2022)
Skin is a frontline organ that is continuously exposed to external stimuli, including pathogens. Various immune cells reside in the skin under physiological conditions and protect the body from the entry of pathogens/antigens by interacting with each other and orchestrating diverse cutaneous immune responses. To avoid unnecessary inflammation and tissue damage during the elimination of external pathogens and antigens, skin possesses regulatory systems that fine-tune these immune reactions. Mast cells (MCs) are one of the skin-resident immune cell populations that play both effector and regulatory functions in the cutaneous immune response. So far, the interleukin-10-mediated mechanisms have mostly been investigated as the regulatory mechanisms of MCs. Recent studies have elucidated other regulatory mechanisms of MCs, such as the maintenance of regulatory T/B cells and the programmed cell death protein-1/programmed cell death-ligand 1-mediated inhibitory pathway. These regulatory pathways of MCs have been suggested to play important roles in limiting the excessive inflammation in inflammatory skin diseases, such as contact and atopic dermatitis. The regulatory functions of MCs may also be involved in the escape mechanisms of antitumor responses in skin cancers, such as melanoma. Understanding and controlling the regulatory functions of skin MCs may lead to novel therapeutic strategies for inflammatory skin diseases and skin cancers.